Incidents that define process safety - Atherton, John (Wiley, 2008)
Incidents That Define Process Safety describes approximately fifty incidents that have had a significant impact on the chemical and refining industries' approaches to modern process safety. Events are described in detail so readers get a fundamental understanding of the root causes, the consequences, the lessons learned, and actions that can prevent a recurrence. There are exhaustive investigative reports about these events, allowing you to apply the resulting safety principles to their current operations.
"Center for Chemical Process Safety."
Keywords: Chemical plants -- Accidents -- United States -- Case studies.; Chemical industry -- United States -- Safety measures.; elektronické knihy; electronic books